2021
DOI: 10.2478/rtuect-2021-0102
|View full text |Cite
|
Sign up to set email alerts
|

Small Hydropower Potential and its Development in Georgia

Abstract: Despite significant achievements in energy development in Georgia, the issue of energy independence is still relevant. The electricity produced in the country cannot meet the growing demands. In addition, Georgia has energy potential, which is not yet fully harnessed, in particular, in terms of hydropower resources. Based on existing studies, only 20–22 % of the hydropower potential is currently harnessed in the country. For a country like Georgia, it is promising to develop hydro resources of small river to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In 2015, the share of renewable energy in the electricity supply basket in Georgia, around 80%, was the highest in the world, most of which was hydroelectric (150). Studies have shown that Georgia has a good potential for wind power (151), in which a 20.7 MW wind power plant in Georgia was launched in 2016 (152), which annually prevents the emissions of 5 tons of greenhouse gases (153). With an annual average of wind speed up to 15 m/s in some places, its energy average production is 4160 GWh/year (154).…”
Section: Georgiamentioning
confidence: 99%
“…In 2015, the share of renewable energy in the electricity supply basket in Georgia, around 80%, was the highest in the world, most of which was hydroelectric (150). Studies have shown that Georgia has a good potential for wind power (151), in which a 20.7 MW wind power plant in Georgia was launched in 2016 (152), which annually prevents the emissions of 5 tons of greenhouse gases (153). With an annual average of wind speed up to 15 m/s in some places, its energy average production is 4160 GWh/year (154).…”
Section: Georgiamentioning
confidence: 99%
“…On the other hand, in Georgia, there are tens of large hydraulic structures with hydropower plants (HPP) in operation. They generate about 90 % of Georgia's electricity production using just about 20 % of the country's hydro energetic potential [9]. This article aims to draw attention to the fact that those structures themselves can serve as an accurate flow-measuring device.…”
Section: Discharge Measurement Networkmentioning
confidence: 99%